On the valuation of property for taxation - O'Brien, Murrough (Statistical and Social Inquiry Society of Ireland, 1879)
In a former paper on valuation I mentioned the fact that in both England and Ireland large country houses are generally assessed at very low rates. This low rating, however, is not confined to country houses; there are many other kinds of property of which the annual value cannot be ascertained by comparing them with similar properties, whose letting value is known. In fact the definition of rateable value as ?the rent which may reasonably be expected?, cannot be truthfully applied to those hereditaments that are not usually let from year to year.
Read before the Society, 18 February 1879
Keywords: Property tax; Valuation of property; Tax reform; 314.15